Kasus Rempang Dalam Perspektif Hukum Militer Dampak Atas Respresifitas Aparat Penegak Hukum - Syabilal Ali; Irwan Triadi (Jurnal Relasi Publik, 2024)
The case of Rempang Island is an example of the many cases of violence perpetrated by repressive law enforcers against civilians in Indonesia, where violence is in direct contact with criminal values. So clear knowledge is needed regarding the impact of authority used improperly by law enforcement officials. This research uses a normative juridical research method with the problem approach used is a statutory approach, a concept analysis approach, and a case approach. The research results reveal that there are limitations for law enforcement officers in carrying out their duties assigned by the state, including preventive measures in providing supervision and security so that the human rights of civilians can still be protected.